Efek Moderasi Size dalam Pengungkapan Sukarela: Bukti Empiris di Bursa Efek Indonesia - Wendy, Wendy (Fakultas Ekonomi dan Bisnis, UNTAN, 2020)
The purpose of this study is to analyze the determinants of voluntary disclosure (VD) by using three non-interaction models and one interaction model. This paper observes four VD